Transverse Load Discrimination in Long-Period Fiber Grating via Artificial Neural Network - F. O. Barino; F. S. Delgado; A. Bessa dos Santos (Journal of Microwaves, Optoelectronics and Electromagnetic Applications, 2020)
Abstract We present a general investigation of a Long-Period Grating (LPG) for transverse strain measurement. The transverse strain sensing characteristics, for instance, the load intensity and azimuthal angle, are analyzed with the data set generated by the LPG sensor and probed by artificial neural network (ANN). Furthermore, we evaluate and compare the predictive performance of the interrogation model considering the square correlation coefficient (R2), root mean square error (RMSE) and mean absolute percentage error (MAPE). The results indicate that the ANN model could be successfully employed to estimate the load intensity and azimuthal angle using a single LPG sensor.